Technology and the pedagogics of learning - Mapuva, Jephias (Cambridge Scholars, 2010)
The book attempts to bring out the prospects and challenges of utilising technology in information dissemination within the education discourse. Primarily, this book addresses the challenges that confront both students and academics who are involved in di.